Clinical utility of level-of-evidence-1 disease forecast cancer biomarkers uPA and its inhibitor PAI-1. (November 2010) - Schmitt, Manfred; Mengele, Karin; Napieralski, Rudolf; Magdolen, Viktor; Reuning, Ute; Gkazepis, Apostolos; Sweep, Fred; Brünner, Nils; Foekens, John; Harbeck, Nadia
The prognostic and/or predictive value of the cancer biomarkers, urokinase-type plasminogen activator (uPA) and its inhibitor (plasminogen activator inhibitor [PAI]-1), determined by ELISA in tumor-tissue extracts, was demonstrated for several cancer types in numerous clinically relevant retrospective or prospective studies, including a multicenter breast cancer therapy trial (Chemo-N0). Consequently, for the first time ever for any cancer biomarker for breast cancer, uPA and PAI-1 have reached the highest level of evidence, level-of-evidence-1. At present, two other breast cancer therapy trials, NNBC-3 and Plan B, also incorporating uPA and PAI-1 as treatment-assignment tools are in effect. Furthermore, small synthetic molecules targeting uPA are currently in Phase II clinical trials in patients afflicted with advanced cancer of the ovary, breast or pancreas.